Human microbiota: A crucial gatekeeper in lung cancer initiation, progression, and treatment - Yuqing Zhou; Tingtao Chen (Medicine in Microecology, 2022)
Lung cancer is becoming one of the most detrimental cancers with the highest morbidity and mortality rate of all cancers, posing a significant burden for the global health system. Nonetheless, the therapeutic efficacy of traditional lung cancer therapies still remains relatively unsatisfying with varied responsiveness and unexpected adverse effects. Fortunately, studies have reported that an intimate relationship might exist between microbiota and lung carcinoma. Notably, microbial dysbiosis might result in changes in the metabolism, induction of immunosuppression, and recruitment of inflammatory factors, thereby driving lung carcinogenesis. Certain microbial strains were identified to be specifically enriched in the lung tumor beds, indicating their predictive role in lung cancer. Furthermore, the particular microbial composition was also proved to potentiate the outcomes of lung cancer therapies, suggesting that lung and gut microbiome were promising to be clinically applied for lung cancer therapy. In this review, we will comprehensively summarize the recent findings on how microbes mediate the initiation, progression, and treatment of lung cancer, illustrating the potential mechanisms and probing into the putative manipulation of microbiota to facilitate lung cancer treatments.